2021
DOI: 10.1111/1365-2745.13656
|View full text |Cite
|
Sign up to set email alerts
|

Higher sample sizes and observer inter‐calibration are needed for reliable scoring of leaf phenology in trees

Abstract: Reliable phenological observations are needed to quantify the impact of climate change on tree phenology. Ground observations remain a prime source of phenological data, but their accuracy and precision have not been systematically quantified. The high subjectivity of ground phenological observations affects their accuracy, and the high within‐population variability of tree phenology affects their precision. The magnitude of those effects is unknown to date. We first explored the inter‐observer variability in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 111 publications
1
16
0
Order By: Relevance
“…For example, Tomescu [67] reported a DOY of 289 for sessile oak in the Dobrina forest, and Tomescu [84] reported a DOY of 273 for sessile oak in the Poieni forest located 360 m from our RAD population, suggesting a delay in leaf senescence of 1.7-4.6 days per decade. As mentioned previously, these differences should be treated with caution, since the phenological observation protocol is not the same, and the influence of inter-observer variability is very high [85]. Similarly, we observed a small delay in the average date of leaf senescence in the reference HEL population (DOY 282) and the FAN comparative trial (DOY 293) compared with nearby sites such as the Bradatel forest (DOY 273) and Casa cu Nuci forest (DOY 289; [84]).…”
Section: Leaf Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tomescu [67] reported a DOY of 289 for sessile oak in the Dobrina forest, and Tomescu [84] reported a DOY of 273 for sessile oak in the Poieni forest located 360 m from our RAD population, suggesting a delay in leaf senescence of 1.7-4.6 days per decade. As mentioned previously, these differences should be treated with caution, since the phenological observation protocol is not the same, and the influence of inter-observer variability is very high [85]. Similarly, we observed a small delay in the average date of leaf senescence in the reference HEL population (DOY 282) and the FAN comparative trial (DOY 293) compared with nearby sites such as the Bradatel forest (DOY 273) and Casa cu Nuci forest (DOY 289; [84]).…”
Section: Leaf Senescencementioning
confidence: 99%
“…These changes in the occurrence of phenological phases are also reflected in the length of the vegetation season [87,[96][97][98], as can be seen in comparisons between our results and those reported previously for bioactive season lengths. Based on observations between 1956-1965, Tomescu [85] found that the vegetation period in sessile oak lasted, on average, 180 days regardless of geographical gradients (200 days at 100 m altitude and 160 at 650 m). Therefore, we can observe a lengthening of the growing season by ca.…”
Section: Leaf Senescencementioning
confidence: 99%
“…the timing of spring phenology with respect to autumn phenology; Keenan and Richardson, 2015). Models of spring phenology regularly outcompete models of autumn phenology by several days when assessed by the root mean square error between observed and modelled dates (4-9 vs. 6-13 days, respectively; Basler, 2016;Liu et al, 2020). 60…”
Section: Introductionmentioning
confidence: 99%
“…While the uncertainty associated with climate projections has been extensively researched (e.g. Palmer et al, 2005;Foley, 2010;Braconnot et al, 2012), so far the uncertainty associated with process-oriented phenology models has only been described in 75 a few notable studies: Basler (2016) compared spring phenology models calibrated per species and per site as well as calibrated per species with pooled sites, Liu et al (2020) compared autumn phenology models with a focus on inter-site and inter-annual variability, and Liu et al (2021) focused on sample size and observer bias in observations of spring and autumn phenology.…”
Section: Introductionmentioning
confidence: 99%
“…The expanded BBCH scale is growing in popularity. Now it has become international and has already been adapted for many different in origin, ecology, and economic use of plants of common and little-known species and agricultural crops, including fruit crops (Danner et al, 2019;Vaidya, 2019;Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%